Isolation, purification and cryopreservation of spermatogonial stem cells from testis of azoospermia patients - Mirzapour, Tooba (2011)
Isolation and proliferation of human spermatogonia stem cells (hSSCs) in vitro will allow powerful new approaches in treatment of selected causes of male infertility. Leukaemia inhibitory factor (LIF) has been considered an essential component for longterm culture of primordial germ cell and its combination with basic fibroblast growth factor (bFGF) has been expected to elicit a much higher effect. The objective of the present study was to develop an in vitro culture system for cellular proliferation of spermatogonia stem cells (SSCs) from the human testes by adding different concentrations of LIF and bFGF and co-culture germ cells on Sertoli cells. Human testis biopsies were routinely obtained from patients diagnosed with maturation arrest of spermatogenesis through the clinical practice of Imam Khomeini Hospital (Tehran, Iran) patients (n=25, average 35.6±0.5 years). Then hSSCs and Sertoli cells were isolated by two- step enzymatic digestion method, plated and grown on DSALectin coated dishes in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum (FCS) at 37°C in 5% CO2 for 5 weeks. The culture groups include (1) SSCs cultured without Sertoli cells, (2) SSCs co-cultured with Sertoli cells (as control group), and (3) SSCs co-cultured with Sertoli cells and adding different concentration of bFGF (0.1, 1, 10 ng/mL) and LIF (1000, 1200, 1500 unit/mL) as experimental groups. Spermatogonial-cell-derived colonies were evaluated based on the number and the diameter of colonies after 10 days of culture and continued every 10 days during 5 weeks culture using an inverted microscope (Zeiss, Germany). Cultured cells were evaluated by RT-PCR using mRNA of Dazl, Oct-4, Nanog, α6-Integrin, β1-Integrin, Piwil2, Stra8, Vasa, Bax and Dmc1genes and examined by immunocytochemistry using anti-Vimentin, anti-CDH1 and anti-Oct-4 to confirm Sertoli cells and spermatogonia stem cells. Effects of cryopreservation on cell viability and proliferation of SSCs in vitro was also evaluated in different stages of culture. The presence of functional spermatogonia stem cells in the culture system was evaluated by xenotransplantation of different concentration of cultured cells in immunodeficient mice testis. The number of colonized seminiferous tubules after transplantation was detected by BrdU fluorescence and Hoechst staining during eight weeks after transplantation. Results showed that spermatogonial-cell-derived colonies were formed in the culture system after one week. In the first group, the average number and diameter of the colonies were significantly lower than in the two other groups (P<0.05). The largest number of colonies was observed in the control group (32.29± 9.15) in day 30. The largest diameter of colonies was formed in combinated doses of 1ng/mL bFGF +1500unit/mL LIF (302.93±37.68). Isolated SSCs were positive for spermatogonial cell markers such as Oct4, Dazl, Stra8, Piwil2, Vasa and α6-Integrin, but negative about Nanog and β1-Integrin Genes. Expression of an apoptotic gene (Bax) was observed approximately 35 days after culture but Dmc1 that is a meiotic gene was not observed in the culture system. Assessment of proliferation ability of SSCs after cryopreservation showed that the number and the diameter of colonies in the co-culture of frozen-thawed SSCs on fresh Sertoli cells was more than co-culture of fresh SSCs on fresh Sertoli cells (19.60± 2.80 and 17.33±2.20 for the number and 269.70±52.10, 204.34± 24.10 for the diameter, respectively). It indicated that cryopreservation of SSCs before culture will increase purified SSCs and they formed many big size colonies in comparison of the control group. Transplantation of hSSCs to infertile mice model testis indicated that these cells have good efficiency for colonization of seminiferous tubules after proliferation in the culture system, however meiotic divisions were not observed eight weeks after transplantation. An ultrastructure study of cultured germ cells showed that many various types of spermatogonia were identified in culture system but were not observed remarkably difference between spermatogonial cells in culture system and testis tissue.